(3HdhZ GdZGjI aj TQM GdcaGjIs - (3GdMSjfj GdMdj, eSde Hf MehO, (B1401 (3g`s ((3GdeDdas)
(3ChdgG (B:s
... (3hCeG GdKGfj (B- (3hgh GdeSei HGdYQV GdfGFj (B- (3agh CjVG KdGKI CbSGe , aGdChd (B- (3gh eG cGf YGQVG HHTjA ChdG hHGdPGJ , HGf dG Jchf gfGc hGSWI CUdG (B..s
(3BNQgG (B:s
... (3hUQjM HYVge EQGOI GdeQMdI GdChdi (B- (3Cj eQMdI GdGSJYeGd (B- (3ceG gh XGgQ ef cdGe GdeUfaGJ hGddg GdYGde hGdMeO ddg QH GdYGdejf (B. (3Jes
(3eHjVI GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
Keywords: (3CUhd Gdabgs